Associations between polygenic risk for anhedonia and functional brain activity during reward processing - Schäfer, Nicholas; Awasthi, Swapnil; Ripke, Stephan; Daniels, Anna; Meyer-Lindenberg, Andreas; Tost, Heike; Heinz, Andreas; Walter, Henrik; Erk, Susanne (Journal of affective disorders, 2026)
Anhedonia is an important symptom in major mental disorders and is difficult to address due to a limited understanding of its neurobiological and genetic underpinnings. Here, we investigated the effect of a polygenic risk score (PRS) for anhedonia on brain activation during a well-established monetary incentive delay (MID) task, while performing functional magnetic resonance imaging. We derived an anhedonia PRS from a large genome wide analysis (n = 375,275) in our sample of 517 subjects. This sample consisted of four subgroups (healthy controls (n = 373), major depressive disorder (n = 57), schizophrenia (n = 39) and bipolar disorder (n = 48)). We tested for correlation between the individual PRS and brain activation during reward and during loss anticipation and feedback. Additionally, we analysed the correlation between PRS and structural volume size of three reward-related brain areas as well as between PRS and anhedonia scores. We showed that increased PRS was associated with decreased activation in bilateral putamen and left middle frontal gyrus during anticipation and decreased activation in the right caudate during feedback across all subgroups. Moreover, a higher PRS was also correlated with lower activation in left middle frontal gyrus during loss anticipation and salience processing. During loss feedback, higher PRS was correlated with hyperactivity of bilateral putamen and right caudate. No significant correlation was found between PRS and brain volume or anhedonia scores. Our results highlight the importance of the striatum and prefrontal cortex in the context of a genetic risk for anhedonia.